Alcohol consumption and mortality from aortic disease among Japanese men: The Japan Collaborative Cohort study. (November 2017) - ,; Tamakoshi, Akiko; Mori, Mitsuru; Kaneko, Yoshihiro; Tsuji, Ichiro; Nakamura, Yosikazu; Iso, Hiroyasu; Yamagishi, Kazumasa; Mikami, Haruo; Kurosawa, Michiko; Hoshiyama, Yoshiharu; Tanabe, Naohito; et al.
Abstract: Background and aims: Only a few population-based prospective studies have examined the association between alcohol consumption and abdominal aortic aneurysm, and the results are inconsistent. Moreover, no evidence exists for aortic dissection. We examined the effect of alcohol consumption on risk of mortality from aortic diseases. Methods: A total of 34, 720 men from the Japan Collaborative Cohort study, aged 40–79 years, without history of cardiovascular disease and cancer at baseline 1988 and 1990 were followed up until the end of 2009 for their mortality and its underlying cause. Hazard ratios of mortality from aortic diseases were estimated according to alcohol consumption categories of never-drinkers, ex-drinkers, regular drinkers of ≤30 g, and >30 g ethanol per day. Results: During the median 17.9-year follow-up period, 45 men died of aortic dissection and 41 men died of abdominal aortic aneurysm. Light to moderate drinkers of ≤30 g ethanol per day had lower risk of mortality from total aortic disease and aortic dissection compared to never-drinkers. The respective multivariable hazard ratios (95% confidence intervals) were 0.46 (0.28–0.76) for total aortic disease and 0.16 (0.05–0.50) for aortic dissection. Heavy drinkers of >30 g ethanol per day did not have reduced risk of mortality from total aortic disease, albeit had risk variation between aortic dissection and abdominal aortic aneurysm. Conclusions: Light to moderate alcohol consumption was associated with reduced mortality from aortic disease among Japanese men. Highlights: Evidence on the effect of alcohol consumption on aortic disease is scarce and inconsistent. Associations of alcohol consumption and fatal aortic diseases were prospectively examined among 34, 720 Japanese men. Light to moderate alcohol consumption was associated with reduced mortality from total aortic disease.